"Twice the Citizen": How Military Attitudes of Superiority Undermine Civilian Control in the United States. (May 2022) - Brooks, Risa; Grewal, Sharan
Civilian control of the military is central to the making of security policy, ensuring that civilian officials and the elected leaders that appoint them oversee and decide military affairs. This paper exposes a challenge to civilian control in the United States that originates in the disparaging attitudes military personnel hold toward civilian society. We argue that when military personnel view military culture as superior, they are more likely to view civilian political leaders as illegitimate and in turn to favor actions that undermine civilian control. We develop a typology of civilian control in which military officers can constrain, contest and limit civilian authority. Our empirical analysis provides strong and consistent evidence of the corrosive effects of military superiority on civilian control across three surveys of U.S. military personnel: the 1998-99 TISS survey of 2901 military officers, a 2014 YouGov of 275 veterans, and an original 2020 survey of 770 West Point cadets.